2015
DOI: 10.17795/rro-5320
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dose Calculation Algorithms of Isogray Treatment Planning System Using Measurement in Heterogeneous Phantom

Abstract: Background: Radiotherapy is a high-energy ionizing radiation treatment for some kinds of cancers. Accuracy and the quality of radiotherapy treatment planning systems depend on the type of dose calculation algorithms that are utilized. There are uncertainties in the calculation of dose distribution, especially in a heterogeneous situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…stated that the TPS cannot accurately calculate the dose in shoulder and penumbra regions [13]. However, other researchers, evaluating the accuracy of dose calculation by different TPSs, have confirmed the inaccuracy of these systems [27], the various calculation algorithms have different levels of inaccuracy [28]. Therefore, the assessment of these regions was made using the GAFCHROMIC EBT3 film as an independent tool.…”
Section: Discussionmentioning
confidence: 99%
“…stated that the TPS cannot accurately calculate the dose in shoulder and penumbra regions [13]. However, other researchers, evaluating the accuracy of dose calculation by different TPSs, have confirmed the inaccuracy of these systems [27], the various calculation algorithms have different levels of inaccuracy [28]. Therefore, the assessment of these regions was made using the GAFCHROMIC EBT3 film as an independent tool.…”
Section: Discussionmentioning
confidence: 99%
“…Golestani et al have investigated the accuracy of the dose by means of a TPS using different computational methods, and the error rate has reported to be <3%. [16] Furthermore, Miften et al have studied the dose distribution of tumor in the prostate, head, neck, and lungs using a TPS based on Clarkson and superposition algorithms. In the study, they found that the error rate was <4%.…”
Section: Discussionmentioning
confidence: 99%
“…The dose distribution is much more complex in the region of heterogeneous tissues, particularly in small fields and the size of the discrepancy escalates [ 5 , 7 ]. A low-density medium, such as the lung in a small field usually leads to challengingly estimating dose.…”
Section: Introductionmentioning
confidence: 99%